Factors Influencing Learning Difficulties in Stoichiometry Among Chemistry Education Students - Monika; Eny Enawaty; Andi Ifriany (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
Learning difficulties in the Basic Chemistry course remain a common problem among chemistry education students, especially in stoichiometry, as reflected in low final examination scores. Therefore, this study aims to analyze the factors contributing to learning difficulties in stoichiometry among chemistry education students in a Basic Chemistry course. This research employed a quantitative descriptive method involving 48 students selected through purposive sampling. Data were collected using questionnaires, interviews, and documentation. Data were analyzed using descriptive percentage analysis to determine the relative contribution of each factor. The results reveal that learning difficulties are influenced by internal and external factors. Internal factors include physical condition (50%), categorized as Poor; physiological function (29%), categorized as Very Poor; interest (29%), categorized as Very Poor; and motivation (32%), categorized as Very Poor. Meanwhile, external factors consist of family environment (22%), in the Very Poor category, campus environment (31%) in the Very Poor category, and community environment (29%) in the Very Poor category. The percentages indicate the relative contribution of each factor to students’ learning difficulties, with physical condition emerging as the most dominant factor affecting students’ understanding of stoichiometry. These findings underscore the need for lecturers to develop more effective learning strategies, increase students’ motivation and interest, and create a supportive learning environment. In addition, students are expected to improve their learning readiness and actively manage their learning conditions in order to better understand stoichiometry.